(untitled) - Majul, Cesar Adib (Quezon City, 1973)
Muslims in the Philippines can be represented peoples who had managed to keep themselves free from foreign invaders at the cost of so much blood, suffering and sacrifice
Keywords: Người Hồi giáo,Muslims; Lịch sử,History; Philippines,Philippines